A multidisciplinary collaborative care model involving family members in the treatment of type 2 diabetes mellitus and associated diabetes distress in young and middle-aged patients - Wang Yan-Ping; Peng Lu-Yao; Yuan Xian-Ming; Chen Ting-Ting; Li Lin; Deng Kai-Qin (Vojnosanitetski Pregled)
Background/Aim. Diabetes mellitus (DM) represents a significant and enduring health concern and, due to various complications arising from inadequate management, leads to disability and mortality. The aim of this study was to examine the impact of the family-engaged multidisciplinary collaborative care (FEC) model on the management of type 2 DM (T2DM) in young and middle-aged patients, considering the presence of DM distress. Methods. The study included 98 patients aged 18 to 59 diagnosed with T2DM and experiencing DM distress. The patients were admitted to the Department of Endocrinology of The First People’s Hospital of Jingzhou, in Hubei province, China, between February and December 2023. Using the random number table method, the patients were randomly assigned to either the intervention group (IG) or control group (CG), each consisting of 49 patients. While both groups received standard care, IG additionally received FEC. We assessed and compared glycated hemoglobin (HbA1c) levels, Diabetes Distress Scale (DDS) scores, Summary of Diabetes Self-care Activities (SDSCA) scores, and body mass index (BMI) between the two groups be-fore the intervention and three months after. Results. Three months post-intervention, IG exhibited lower HbA1c levels (6.02 ± 0.63 vs. 6.81 ± 0.85) and DDS scores (25.27 ± 2.70 vs. 34.24 ± 4.46) while demonstrating higher SDSCA scores (30.69 ± 1.91 vs. 25.03 ± 2.13) compared to CG. Additionally, the BMI of patients in IG measured 23.83 ± 2.51 kg/m2, which, compared to the BMI of CG (25.64 ± 3.68 kg/m2), was statistically significant (p < 0.05). Conclusion. The FEC model demonstrated efficacy in lowering HbA1c levels and BMI, mitigating DM distress, and enhancing self-care capabilities among young and middle-aged patients with T2DM experiencing DM-related distress.